Infinity pool [videorecording (DVD)] - Cronenberg, Brandon; Skarsgård, Alexander; Goth, Mia, 1993-; Coleman, Cleopatra, 1987-; Lespert, Jalil; Brugel, Amanda, 1978-; Ralston, John, 1964-; Ricketts, Jeffrey; Boulton, Caroline; Kretschmann, Thomas, 1962- (Decal, 2023)
James and his wife Em have escaped the city for an all-inclusive vacation at a tropical resort. Despite having come to the island of Li Tolqa to cure his writer's block, James finds himself more uninspired than ever until he meets fellow tourists, Gabi and Alban. James is immediately attracted to their glamorous lifestyle and lust for adventure. They invite James and Em on a day trip to a local beach, usually off-limits to tourists, but an accident throws their entire holiday into chaos.